Food-based multisensory stimulation ameliorates cognitive impairment after mild traumatic brain injury in male rats by modulating intestinal and brain inflammation - Yuhan Wei; Hanif Ullah; Guangneng Liao; Xue Xiao; Jiang Yao; Qiujing Du; Qijie Li; Ka Li (PLoS ONE, 2026)
Mild traumatic brain injury (mTBI) often leads to cognitive impairment (CI), with neuroinflammation and gut microbiota dysbiosis playing pivotal roles in its pathogenesis. This study aimed to investigate whether food-based multisensory stimulation could ameliorate cognitive deficits in mTBI rats via modulation of the gut–brain axis. Using a rat model of mTBI, we demonstrated that food-based multisensory stimulation significantly improved spatial and recognition memory, as evidenced by performance in the Morris water maze and novel object recognition tests, and reduced serum biomarkers of neurological injury (NSE, S100β). Gut microbiota analysis revealed that sensory stimuli restored microbial balance, increasing beneficial taxa such as Ruminococcaceae and reducing pathogenic genera such as Alistipes , Prevotella . Concurrently, senso.ry stimulation increased fecal and serum levels of short-chain fatty acids (SCFAs), particularly butyrate, which were associated with reduced gut and neuroinflammation. In vitro, butyrate supplementation exhibited significant anti-inflammatory effects, promoting M2 microglial polarization and reducing pro-inflammatory cytokines (TNF-α, IL-1β). Histological analyses further revealed neuroprotective effects, preserving neuronal density in the hippocampus and cortex. These findings suggest that multisensory stimulation may mitigate CI post-mTBI by restoring gut microbiota homeostasis, enhancing butyrate production, and attenuating neuroinflammation. This non-invasive approach holds promise for cognitive rehabilitation in patients with mTBI, although further research is needed to elucidate its long-term effects and translational potential.